ANALISIS DAN STRATEGI SUPPLY CHAIN DISTRIBUSI BARANG BERBASIS BLOCKCHAIN DAN ALGORITHMA GENETIKA - Hartanto, Agus; Daru, April Firman (UNIVERSITAS STEKOM, 2025)
The development of the digital era demands a transformation in supply chain management to face increasingly complex challenges. Blockchain and genetic algorithms emerge as innovative solutions capable of enhancing efficiency, transparency, and resilience in the supply chain. Blockchain offers a secure and transparent decentralized system, while genetic algorithms provide an optimal approach for scheduling and coordination. The integration of these two technologies has the potential to create a more efficient, responsive, and sustainable supply chain system. This research aims to formulate a distribution strategy for goods based on blockchain and genetic algorithms, making a significant contribution to the development of supply chains in the Industry 4.0 era.